The Research Council of Norway’s publication grants for scholarly journals: present status and the road ahead - Schjølberg, Rune Rambæk (Septentrio Conference Series, 2014)
The Research Council of Norway’s publication grant scheme has since 1993 contributed to the publication of scholarly journals in the humanities and social sciences. Presently 44 Norwegian journals receive support from the Councils Publications committee. Through the Nordic Publications Board (NOP-HS) RCN also contributes to the publication of 41 Nordic scholarly journals. This presentation will focus on the challenges facing new and existing business models for scholarly journals from the Research council’s point of view, including comments on the new business model proposed by Gunnar Sivertsen.